The fitting book : make sewing pattern alterations and achieve the perfect fit your desire - Dunham, Gina Renee, author (Switzerland : Gina Renee Designs, 2021)
"Think of how happy, proud, and accomplished you feel when you have sewn an outfit, it fits, and you love it. Many people struggle with the standard sizing of commercial or indie sewing patterns. The standard measurements often lead to fitting issues. This garment fitting guide will help you adjust sewing patterns to achieve the perfect fit you desire. This fitting book covers tops, pants, and skirts. There are visual sketches and links to simple videos to help during each step of the 3-part fitting process. Here's how it works: A) Identify the fitting issue. B) Pin, cut, & tape the fitting sample. C) Correct the sewing pattern. Stop wasting time and money sewing clothes that don't fit well. It's time to sew clothes you love that fit." - back cover
First steps in assessing the fit -- Neckline corrections -- Across shoulder corrections -- Across front and across back corrections -- Armhole and raglan sleeve corrections -- Set-in sleeve topics and corrections -- Bust corrections -- Back draglines and hemline corrections -- Skirts, dresses, and pants corrections -- Fitting pants -- Diagonal draglines demystified -- Congratulations! You made it fit!
"...This book includes links to fitting videos for every pattern alteration." - back cover
In English text.
Keywords: Women's clothing; Sewing -- Handbooks, manuals, etc; Tailoring (Women's).; Dressmaking -- Patterns; Machine sewing; Clothing and dress measurements